Asymmetric phthalocyanine compounds in the structure D-π-A containing cyano groups: Design, synthesis and dye-sensitized solar cell applications - Karadogan, Betul; Erden, Ibrahim; Berber, Savas (SAGE PUBLICATIONS INC, 2021)
In this study, asymmetric zinc phthalocyanine compounds with Donor-pi-Anchor (D-pi-A) property that enable the movement of electrons in molecular structure in one direction were synthesized. Phthalocyanines were designed to ensure electron mobility within the molecule and to facilitate the transfer of electrons to the TiO2 layer. The synthesized asymmetric zinc phthalocyanines (ZnPc-1 and ZnPc-2) are molecules with three donor biphenyls and one anchor aldehyde group and three acceptor/anchor cyano and one anchor aldehyde group, respectively. The effect of biphenyl and cyano groups on cell efficiency with aldehyde anchor group was investigated. The structure of the synthesized phthalocyanines was characterized by Fourier Transform Infrared Spectrometry (FTIR), Mass Spectrometry (MS), UV-vis, Fluorescence spectroscopy. The experimentally calculated optical band gap values were supported by the values found by Density Functional Theory (DFT) calculations. dye sensitive solar cells were measured and the efficiencies were evaluated with reference to the N719 standard dye. In the solar cell measurements of the designed phthalocyanines, the structure containing the cyano group has been given a higher photovoltaic cell thanks to the higher short circuit photo-current (Jsc). In this way, the highest power conversion efficiency value was achieved among the cyano group molecules.
Keywords: Dye-sensitized solar cell; Zn(II); cyano anchor; asymmetric pc; ANCHORING GROUPS; TIO2; PERFORMANCE; EFFICIENCY; BRIDGE; Chemistry